Economic policy and state intervention: selected papers of T.N Srinivasan - Narayana,N. S. S.(ed.) (New Delhi, 2002)
This collection brings together, for the first time, T.N. Srinivasan's classic theoretical writings (some co-authored with Jagadish Bhagwati) and his work on issues relevant to developing countries, especially India. His work on GATT and the Uruguay Rounds with reference to developing countries is very well known and is the highlight of this volume. His analysis, over the years, of India's development strategy including issues like poverty, agricultural backwardness, income distribution, role of development strategy, democracy and markets and India as a nuclear power, forms the rest of the collection.
Keywords: Economic policy-India